Epidemiology of prostate cancer in Asian countries - Kimura, Takahiro; Egawa, Shin (International journal of urology, 2018)
The incidence of prostate cancer has been increasing worldwide in recent years. The GLOBOCAN project showed that prostate cancer was the second most frequently diagnosed cancer and the fifth leading cause of cancer mortality among men worldwide in 2012. This trend has been growing even in Asian countries, where the incidence had previously been low. However, the accuracy of data about incidence and mortality as a result of prostate cancer in some Asian countries is limited. The cause of this increasing trend is multifactorial. One possible explanation is changes in lifestyles due to more Westernized diets. The incidence is also statistically biased by the wide implementation of early detection systems and the accuracy of national cancer registration systems, which are still immature in most Asian countries. Mortality rate decreases in Australia, New Zealand and Japan since the 1990s are possibly due to the improvements in treatment and/or early detection efforts employed. However, this rate is increasing in the majority of other Asian countries. Studies of latent and incidental prostate cancer provide less biased information. The prevalence of latent and incidental prostate cancer in contemporary Japan and Korea is similar to those in Western countries, suggesting the influence of lifestyle changes on carcinogenesis. Many studies reported evidence of both congenital and acquired risk factors for carcinogenesis of prostate cancer. Recent changes in the acquired risk factors might be associated with the increasing occurrence of prostate cancer in Asian countries. This trend could continue, especially in developing Asian countries.